A Life Pleasing to God: The Spirituality of the Rules of Saint Basil - Batchelor, Stephen G. (Cistercian studies quarterly, 2003)
Reviews the book "A Life Pleasing to God: The Spirituality of the Rules of Saint Basil," by Augustine Holmes.